2017
DOI: 10.3390/rs9060563
|View full text |Cite
|
Sign up to set email alerts
|

Archaeological Application of Airborne LiDAR with Object-Based Vegetation Classification and Visualization Techniques at the Lowland Maya Site of Ceibal, Guatemala

Abstract: Abstract:The successful analysis of LiDAR data for archaeological research requires an evaluation of effects of different vegetation types and the use of adequate visualization techniques for the identification of archaeological features. The Ceibal-Petexbatun Archaeological Project conducted a LiDAR survey of an area of 20 × 20 km around the Maya site of Ceibal, Guatemala, which comprises diverse vegetation classes, including rainforest, secondary vegetation, agricultural fields, and pastures. We developed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 48 publications
0
73
0
Order By: Relevance
“…Overall, approximately 165 km 2 within the study area have either been used as training samples, subsequently "ground-truthed," or both (Table 3); that is, 7.7% of the entire PLI survey region has been verified through ground survey, although mapped areas were not uniformly distributed (Table 3). Moreover, all field teams within the PLI study region have ground-validated features belonging to every class reported on here: buildings of various types, defensive features, upland and wetland agricultural features, causeways, canals, and reservoirs.…”
mentioning
confidence: 99%
“…Overall, approximately 165 km 2 within the study area have either been used as training samples, subsequently "ground-truthed," or both (Table 3); that is, 7.7% of the entire PLI survey region has been verified through ground survey, although mapped areas were not uniformly distributed (Table 3). Moreover, all field teams within the PLI study region have ground-validated features belonging to every class reported on here: buildings of various types, defensive features, upland and wetland agricultural features, causeways, canals, and reservoirs.…”
mentioning
confidence: 99%
“…We have found the bonemap to be one of the most effective visualizations for identifying architecture, although features such as depressions and drainages are most apparent in the bare-earth hillshade visualization. We therefore retain different visualizations, including slope and aspect rasters, for comparison in ArcGIS and will continue to experiment with alternative visualization methods (e.g, the Red Relief Image Map [Inomata et al 2017] and Prismatic Openness [Canuto et al 2018]). Analysts mark potential features on the master GIS map by creating "go-to points" in a point shapefile.…”
Section: Initial Laboratory Analysis and Preparationmentioning
confidence: 99%
“…Chiba, B. Hasi 2016). Other versions of red relief are combination of hillshade (one direction) and slope (M. Doneus, T. Kühteiber 2013) and combination of SVF (gray) and red slope overlay (T. Inomata et al 2017). Here we presented another version which is a combination of red slope base layer (stretch with 2% clip) with two directional hillshade overlay (stretch to min-max, 70% transparency, blending mode: normal) ( fig.…”
Section: Red Relief Visualizationmentioning
confidence: 99%